Matching Inhaler Devices with Patients: The Role of the Primary Care Physician - Alan Kaplan; David Price (Canadian Respiratory Journal)
Poor inhaler technique and nonadherence impair the efficacy of medications for asthma and chronic obstructive pulmonary disease (COPD). A range of factors, including age, dexterity, inspiratory capacity, cognitive ability, health literacy, and ethnicity, can impact a patient’s ability and intention to use their device. Treatment success can also be influenced by patient preferences and perceptions. Therefore, it is important that healthcare professionals effectively match inhaler devices to individual patients’ needs and abilities and empower patients by including them in treatment decisions. Physicians must, therefore, fully understand the characteristics of each device, as well as their patients’ demographic characteristics and comorbidities. Following device selection, patient training and education, including a physical demonstration of the device, are key to eliminate any critical errors that may impact on health outcomes. Inhaler technique should be frequently rechecked. This review will examine the important role of primary care providers in the selection of appropriate inhaler devices and provision of training for patients with COPD and asthma to optimize correct inhaler use and adherence. An overview of the key features of available devices and of the factors to consider when selecting devices will be provided in the context of current asthma and COPD guidelines.